Penerapan Multimedia TAVAGIS Berbasis Prezi dalam Pembelajaran Kurikulum 2013 bagi Guru Sekolah Dasar di Kabupaten Kuningan - Agatha Kristi Pramudika Sari; Dyah Puteria Wati (Universitas Mathla'ul Anwar Banten, 2019)
APPLICATION OF PREZI-BASED TAVAGIS MULTIMEDIA IN LEARNING CURRICULUM 2013 FOR ELEMENTARY SCHOOL TEACHERS IN KUNINGAN REGENCY. The curriculum currently being implemented in elementary schools in Indonesia is the 2013 curriculum. One of the problems faced regarding the implementation of the 2013 curriculum is the lack of mastery of information and technology (IT) by teachers, due to learning habit patterns that still do not consider IT's role in improving quality learning. Though teachers are required to master IT in this technological era. This community service activity is intended for fourth grade teachers in elementary schools in Kuningan District, Kuningan Regency. The purpose of this training is to improve the skills of teachers in the IT field, in making and implementing Prezi-based TAVAGIS Multimedia in 2013 elementary school curriculum learning. The method of implementing this activity consists of several stages, namely: 1) Planning which includes partner surveys, training licenses, preparation of training modules, training preparation and coordination, and program socialization, 2) Implementation of PKM activities which include training on Prezi-based TAVAGIS multimedia development and use assistance multimedia that has been made, 3) Evaluation and follow-up. Based on the results of observations and quisioner, training in making and assisting the implementation of Prezi-based TAVAGIS multimedia runs smoothly and some obstacles that arise can be resolved so that this activity can improve the knowledge and skills of making Prezi-based TAVAGIS multimedia, thus helping teachers to create interactive, interesting, and fun learning.